PENGARUH MOTIVASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN YAYASAN DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH NURUL FATA BONDOWOSO - Usrotul Hasanah; Deky Wahyudi (ACTON, 2017)
The purpose of the study to determine the influence of motivation, partial and simultant communication to the performance of employees salafiyah boarding school foundation salafiyah syafi'iyah Nurul Fata Bondowoso . This type of research uses a quantitative research approach. The sample was done by Proportionate Stratified Random Sampling technique as many as 140 respondents. The independent variables in this research are Motivation (X1) and Communication (X2). Dependent or dependent variable (Y) is employee performance. The method of analysis used in this study is the classical assumption test and multiple linear regression. Partially and simultaneously Motivation and Communication have an effect on to Performance of salafiyah boarding school foundation salafiyah syafi'iyah Nurul Fata Bondowoso